Challenging Behaviour in Secondary School Students: Classroom Strategies for Increasing Positive Behaviour - Kate Browne (New Zealand Journal of Teachers' Work)
To assist in developing an evidence base in the area of behaviour management in classrooms, a systematic review of strategies to increase the positive behaviour of secondary school students with challenging behaviour in the general education classroom was undertaken. Educators have identified challenging behaviour as a major concern and many teachers report feeling ill-equipped to assist students who exhibit challenging behaviour. By not addressing challenging behaviour during secondary school, young people could face a number of adverse outcomes during adulthood. The objective of this review is to provide teachers with practical evidence-based strategies to address commonly occurring challenging behaviours, in order to increase the learning and social outcomes of students. From an extensive search of electronic databases, selected journals, and reference lists, 10 primary research articles met the selection criteria of this review and were critically evaluated. It was found that the use of positive reinforcement approaches were effective for increasing positive behaviour. The importance of clear, positive communication between students and teachers was shown to be evident, indicating a number of valuable implications for policy and practice.